Cara Pengelolaan Limbah Kopi - Fadilla, Audia; Arahma, Alya; Pakpahan, Enni Halimatusa’diyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Coffee (Coffea sp.) has great potential in providing foreign exchange, making it a very important plantation crop for the economic growth of the Indonesian community. The main purpose of this publication is to learn how to manage coffee waste from various coffee components produced by the people of Indonesia. The chosen research methodology is qualitative research with a literature study. The study findings show that Indonesian coffee waste has various advantages that can be utilized by the surrounding community, such as processing coffee waste into compost, managing coffee into cascara tea, using coffee as animal feed, turning coffee fruit into coffee jam, and organic fertilizer from coffee pulp.